The Analysis of Slang in Fast And Furious 4 Movie - Prastiawan, IB Maha Adi Prastiawan; Candra, Komang Dian Puspita; Santika, I Dewa Ayu Devi Maharani (Institut Pariwisata dan Bisnis Internasional, 2023)
This study entitled The Analysis of Slang in Fast and Furious 4 Movie. The aims of this study to find out the function of slang word that used in Fast and Furious 4 Movie. The analysis concerns with the slang word that occur in the movie. This study used qualitative method and the data collection was based on observation method by downloading the movie and movie script, watching the movie, looking through the scene and taking note. The theory that used in this analysis is theory by Leech (1981) and Chapman (2007) to find out type of slang word that occurs in Fast and Furious 4 Movie. The study concludes that the primary slang word is mostly than secondary slang word on Fast and Furious 4 Movie based on the film. This study reveals that there are 25 slangs which is found in Fast and Furious 4 Movie. From the data, there are 22 primary slangs and 3 secondary slangs found. The meaning of slang mostly related to informational function which is focused on the speaker tends to inform something to the other characters in movie, which from the analysis can be concluded the meaning of slang are various.